2007
DOI: 10.1590/s0034-89102007000400011
|View full text |Cite
|
Sign up to set email alerts
|

Problemas de saúde mental entre jovens grávidas e não-grávidas

Abstract: OBJECTIVE:To estimate the prevalence of mental health problems in primiparous adolescents and to compare their mental health profi le with the profi le of sexually active adolescents who have never gotten pregnant. METHODS:Cross-sectional study that compared two groups of adolescents aged 13 to 17 years from a city in Southern Brazil, 2003Brazil, -2004. The sample included 207 primiparous who attended prenatal care programs in urban public services, and 308 sexually active students from state public schools w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1
11

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 16 publications
1
12
1
11
Order By: Relevance
“…Low self-esteem, lower wish to live, depression and anxiety (14)(15)19,(22)(23)(24)(33)(34)38,48,62) Attention-defict hyperactivity disorder, oppositional/conduct disorder somatic complaints (11)(12)(13)23,25,59,62) . Self-aggression or suicide attempt; suicidal ideation (10,(13)(14)25,56) Sadness/loneliness feelings (10,34,58) Insomnia, fatigue, forgetfulness, irritability, difficulty concentrating and feelings of worthlessness (11)(12) Internalizing and externalizing behaviors (23,25) Aggression/ high levels of anger/interpersonal problems (27) Neurotic disorders (28) Abdominal obesity/ self-image (35) Need to feel pleasure (37) 43.4…”
Section: Individualmentioning
confidence: 99%
See 1 more Smart Citation
“…Low self-esteem, lower wish to live, depression and anxiety (14)(15)19,(22)(23)(24)(33)(34)38,48,62) Attention-defict hyperactivity disorder, oppositional/conduct disorder somatic complaints (11)(12)(13)23,25,59,62) . Self-aggression or suicide attempt; suicidal ideation (10,(13)(14)25,56) Sadness/loneliness feelings (10,34,58) Insomnia, fatigue, forgetfulness, irritability, difficulty concentrating and feelings of worthlessness (11)(12) Internalizing and externalizing behaviors (23,25) Aggression/ high levels of anger/interpersonal problems (27) Neurotic disorders (28) Abdominal obesity/ self-image (35) Need to feel pleasure (37) 43.4…”
Section: Individualmentioning
confidence: 99%
“…Domestic violence with physical punishment experience (23)(24)31,56) Difficulties with family relationships (parents and siblings) (13,31,61) Parents and friends influence to use drugs (14,56) Low emotional support at home during childhood (15,60) Alcohol abusive parents (47,54) Parents divorce 0, 19)to de tristeza; átricos. (19) Family financial problems (38) Parents with low well-being levels (52) Bad experience of family communication (52) Parents that live with or died of HIV/Aids (60) 26.4…”
Section: Family Relatedmentioning
confidence: 99%
“…a study that reported an antenatal depression prevalence of 37.9%) reported prevalence rates ranging from 13% to 20.8% 4,7,12,14,26,29,37 . The validity of these findings still needs to be established as the majority of these studies focused on pregnant adolescents 4,26,29,37 and women receiving prenatal care in obstetric out-patient clinics in hospital settings 7,12,14,26,29 . These samples are likely to be biased because women with high-risk pregnancies are more likely to seek prenatal care in hospitals.…”
Section: Introductionmentioning
confidence: 98%
“…These samples are likely to be biased because women with high-risk pregnancies are more likely to seek prenatal care in hospitals. Furthermore, one of these studies used a small sample 13 and several used depression screenings rather than diagnostic instruments 4,12,14,37 .…”
Section: Introductionmentioning
confidence: 99%
“…A literatura sobre essa temática é ampla, sendo que a maior parte dos estudos tem delineamento transversal e quantitativo, enfatizando aspectos negativos da vivência, enquanto os estudos qualitativos tendem a revelar aspectos positivos e adaptativos em relação à maternidade. Dentre alguns dos problemas comumente relacionados à esta condição, destacam-se os riscos para a saúde de mãe e filho, o baixo nível socioeconômico, o início precoce da menarca e relações sexuais, abandono escolar, violência sexual entre mulheres com menos de 14 anos, sofrimento psíquico e dificuldades na adoção de comportamentos contraceptivos, que se constituem como experiências subjetivas e graduais, adquiridas ao longo do tempo (Brandão & Heilborn, 2006;Caputo & Bordin, 2007;Cavasin et al, 2004;Cerqueira-Santos, Paludo, Schirò, & Koller, 2010;Levandowski, Piccinini, & Lopes, 2008;Sabroza, Leal, Souza, & Gama, 2004;Taquette, 2008).…”
unclassified